Association of Self-Rated Health in Pregnancy With Maternal Childhood Experiences, Socioeconomic Status, Parity, and Choice of Antenatal Care Providers: Cross-Sectional Study - Bjarne Austad; Gunnhild Åberge Vie; Mari Hegnes Hansen; Hanna Sandbakken Mørkved; Linn Okkenhaug Getz; Bente Prytz Mjølstad (JMIR Formative Research)
Abstract BackgroundDuring pregnancy, self-rated health (SRH) and self-rated mental health (SRMH) are key indicators of health status and predictors of future health care needs. The relationship between pregnant women’s health perceptions and their choice of antenatal care providers, midwives, or general practitioners (GPs) is not known. Factors like childhood experiences and socioeconomic status are important determinants of health throughout life. Understanding these health determinants can help health care providers better address the diverse needs of pregnant women. ObjectiveThis study aims to assess how SRH and SRMH during pregnancy are associated with maternal childhood experiences, socioeconomic status, parity, and antenatal care provided by midwives or GPs. MethodsAn anonymous, web-based cross-sectional survey was conducted from January to March 2022 among pregnant women in Norway, distributed via Facebook and Instagram. The survey included questions on SRH, SRMH, socioeconomic status, childhood perceptions, and antenatal program participation. Pearson’s chi-squared test and logistic regression models were used to explore associations and estimate odds ratios for good SRH and SRMH. ResultsAmong 1402 participants, 94.7% (1328/1402) reported good or very good health before pregnancy, dropping to 67.8% (950/1402) during pregnancy (PPPPPP ConclusionsA difficult maternal childhood, low socioeconomic status, and having given birth before were associated with poorer SRH and SRMH during pregnancy. Both midwives and GPs played vital roles in providing antenatal care, though few women received antenatal care exclusively from GPs. The likelihood of physician involvement in care increased slightly with worsening health.